A remarkable new species of the sharpshooter genus Erythrogonia Melichar (Hemiptera: Cicadellidae: Cicadellini) from southern Brazil with taxonomic notes on the genus - Mejdalani, Gabriel; Cavichioli, Rodney R. (Zootaxa, 2016)
A new species of Erythrogonia Melichar, 1926, E. brunnea, is described and illustrated based on specimens from the state of Paraná, southern Brazil (Atlantic Forest). The new species can be distinguished from the other ones of the genus by the male genitalia and color pattern, especially by the presence of a conspicuous pale yellow arc behind the ocelli that continues posteriorly as a pair of lateral longitudinal stripes over the pronotum and forewings to the base of the third apical cell. Although E. brunnea does not show the typical color pattern of Erythrogonia species, features of both the male and female genitalia justify its assignment to this genus (including a dorsal sclerite located at the base of the rami of the ovipositor valvulae II). Two taxonomic changes are proposed: (1) the monotypic genus Spinagonalia Cavichioli, 2008 is synonymized with Erythrogonia (E. separata Melichar, 1926 = S. rubrovittata Cavichioli, 2008 syn. nov.); (2) Erythrogonia jucunda (Walker, 1851) is transferred to Pawiloma Young, 1977 (P. jucunda (Walker, 1851) comb. nov. = P. rubra Cavichioli, 1998 syn. nov.).